The role of intangible factors in the intention of repeating a tourist destination - Vieira, Elvira (2020)
Little attention has been paid towards the intangible factors influencing tourism loyalty. Among these are usually the experiences during the stay, the engagement or the cultural identification with the destination. In this paper we explored the relationship of these underlying intangible factors with the intention to return to a destination. We used a sample of 958 tourists, who answered to a questionnaire applied in the city of Porto, Portugal. Results show that engagement and cultural identification with the destination are positively linked with the intention to return. We also observe a positive relationship between intention to return and specific tourist perceptions concerning the destination, namely social responsibility, available experiences and cultural heritage. Policy makers should focus on intangible factors in order to develop strategies to foster attractiveness and promote the uniqueness of tourist destinations. The central challenge to the sector’s stakeholders is related to the experiences and tourist engagement.